Pengaruh Budaya Organisasi, Komunikasi Interpersonal dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to ascertain how employee performance at PT. Charoen Pokphand Indonesia Food Division Tabanan is impacted by organizational citizenship behavior, interpersonal communication, and organizational culture. The population is 75 employees, so the sampling method used is the census method, where a research sample is drawn from the entire population The following techniques are used to collect data: questionnaires, literature, documentation, interviews, and observation. Multiple linear regression analysis was the analysis method employed in this investigation. The study's findings indicate that, to a partially positive and significant extent, organizational culture affects employee performance. Employee performance is somewhat improved and significantly impacted by interpersonal communication. The performance of employees is positively and significantly impacted by organizational citizenship behavior. Employee performance is positively and significantly impacted by organizational culture, interpersonal communication, and organizational citizenship behavior all at the same time. The researcher made a recommendation based on the study's findings: the head of PT. Charoen Pokphand Indonesia Food Division Tabanan can inspire employees with incentives, improve relationships among coworkers, and offer socialization and training about the business.